2007
DOI: 10.1080/01626620.2007.10463440
|View full text |Cite
|
Sign up to set email alerts
|

The Cooperating Teacher I's: Effective Mid-Lesson Responses to Student Teachers' Critical Teaching Incidents

Abstract: When student teachers experience difficulty during lesson implementation, seasoned cooperating teachers choose among 6 alternative strategies by which to assist. Collectively called cooperating teacher I'S, the strategies are as follows: ignore, intervene, interject, interact, interrupt, and intercept. Appropriate use of these strategies can be taught directly or made more explicit to cooperating teachers as a means to facilitate quick resolution of problems; maintenance of student teacher confidence, self-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…While important to the development of mentors and the growth of student teachers, these practices do not reveal what educative mentors do to provide intentional learning experiences for their student teachers "inside the action" of teaching, when students are present (Schwille, 2008, p. 155). Moreover, examples of mentoring that happen "inside" teaching often highlight instances of mentor teachers taking action during a novice teacher's classroom instruction, such as providing "subtle interventions" or "quick interjections" (Gardiner, 2017, p. 65;Post, 2007), often to guide, or redirect, the students ( Jaspers et al, 2018). Such examples provide valuable insights into mentoring that happens between mentor and novice teachers, yet fall short of considering how educative mentoring extends into mentoring inside the action that occurs in the room where it happens.…”
Section: Reflections From the Roommentioning
confidence: 99%
See 1 more Smart Citation
“…While important to the development of mentors and the growth of student teachers, these practices do not reveal what educative mentors do to provide intentional learning experiences for their student teachers "inside the action" of teaching, when students are present (Schwille, 2008, p. 155). Moreover, examples of mentoring that happen "inside" teaching often highlight instances of mentor teachers taking action during a novice teacher's classroom instruction, such as providing "subtle interventions" or "quick interjections" (Gardiner, 2017, p. 65;Post, 2007), often to guide, or redirect, the students ( Jaspers et al, 2018). Such examples provide valuable insights into mentoring that happens between mentor and novice teachers, yet fall short of considering how educative mentoring extends into mentoring inside the action that occurs in the room where it happens.…”
Section: Reflections From the Roommentioning
confidence: 99%
“…Specifically, Travis appeared to enact characteristics of educative mentoring different from how we considered mentoring "inside" teaching. Rather than provide "subtle interventions" or "quick interjections" (Gardiner, 2017, p. 65;Post, 2007), Travis described intentionally making visible his thoughts and decision-making processes during lessons he taught and co-taught with Erick. To better understand these educative mentoring moves made in the moment of teaching, we invited Travis and Erick to participate in a research study that would probe these educative mentoring exchanges taking place in the unique context of their shared classroom.…”
Section: Participantsmentioning
confidence: 99%
“…According to Post (2007), the task to help cooperating teachers mentor more effectively falls on the shoulders of the university supervisors. Here again, cooperating teachers' needs may vary according to their prior preparation and experience.…”
Section: Discussionmentioning
confidence: 99%
“…-Nemser (2001) observed that supervisors need to work closely with cooperating teachers and student teachers, and when they do not, there is no sharing of expertise. Horton and Harvey (1979), Post (2007), and Smith (2007) also believe that university supervisors can assist cooperating teachers in the various approaches to planning and teaching. However, it is vital to acknowledge the importance of the university supervisor in this complex triad.…”
Section: Types Of Preparation Cooperating Teachers Receivedmentioning
confidence: 99%
“…The second challenge was deciding whether to intervene during STs' lessons. This last challenge has been described to some extent by Post (2007). She described six effective mid-lesson interventions of MTs, namely ignore, intervene, interject, interact, interrupt and intercept.…”
Section: Challenges In Simultaneously Performing the Mentor And Teacher Rolementioning
confidence: 99%